Nonpharmacological therapies for cognitive enhancement in Parkinson's disease: applying old interventions in a new setting?. (December 2013) - Sindhi, Amit; Leroi, Iracema
SUMMARY Parkinson's disease (PD) is a neurodegenerative disorder characterized by motor and non-motor features. Among non-motor features, cognitive impairment and the development of dementia is common. Current pharmacological treatment for cognitive impairment is limited and is only licensed for established dementia. Furthermore, pharmacological treatment may not be tolerated by some patients. Therefore, alternative treatment strategies such as nondrug cognition-enhancing therapies may have a role in PD. This article outlines therapies that have been widely used in non-PD dementia and makes recommendations for how they can be adapted to the PD setting.